Actively Tunable Visible Surface Plasmons in Bi2Te3 and their Energy‐Harvesting Applications. Issue 16 (29th February 2016) - Zhao, Meng; Zhang, Jie; Gao, Nengyue; Song, Peng; Bosman, Michel; Peng, Bo; Sun, Baoquan; Qiu, Cheng‐Wei; Xu, Qing‐Hua; Bao, Qiaoliang; Loh, Kian Ping
Abstract : Hexagonal Bi2 Te3 nanoplates support visible‐range surface plasmons, of which the resonance energy is tuned as wide as 400 nm by Se doping and the resonance intensity is modulated by utilizing the phase change between the crystalline and amorphous states. The potential of Bi2 Te3 for reconfigurable plasmonics, plasmon‐enhanced solar cells, and photoluminescence is demonstrated.